2018
DOI: 10.1038/s41371-018-0075-9
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative mean arterial pressure and risks of adverse cardiac and cerebrovascular events: a prospective cohort study of 53,813 adults

Abstract: The association between cumulative mean arterial blood pressure (MAP) and risks of adverse cardiac and cerebrovascular events (CCVEs) has not been characterized. This prospective cohort study included 53,813 participants, free of prior myocardial infarction or stroke in or before 2010 (baseline) from a community-based cohort including 101,510 participants. Cumulative MAP was defined as the summed average MAP for each pair of consecutive examinations multiplied by the time interval with the data from previous s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Third, this study adjusted for comprehensive confounding factors (including demographic characteristics, clinical measurement indicators, lifestyle variables and related disease history) and used the sensitivity analysis to further eliminate some potential effects on study results. Fourth, our large and long-term study made up for the shortcomings of previous studies on cumulative MAP cohort, and based on Cui et al ‘s study, 10 we directly targeted the population of hypertensive patients to further study the role of cumulative MAP, and expanded the specific characteristics of high-risk group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Third, this study adjusted for comprehensive confounding factors (including demographic characteristics, clinical measurement indicators, lifestyle variables and related disease history) and used the sensitivity analysis to further eliminate some potential effects on study results. Fourth, our large and long-term study made up for the shortcomings of previous studies on cumulative MAP cohort, and based on Cui et al ‘s study, 10 we directly targeted the population of hypertensive patients to further study the role of cumulative MAP, and expanded the specific characteristics of high-risk group.…”
Section: Discussionmentioning
confidence: 99%
“…Cumulative MAP was defined as the sum of MAP from each consecutive examination multiplied by the time interval between the two successive examinations. 10 Participants’ BP was measured monthly between June 2010 and May 2011 to observe long-term fluctuations in BP levels, and cumulative MAP was calculated using these one-year BP record data. Cumulative BP exposure model was calculated as follows: cumulative MAP = [(MAP 1 +MAP 2 )/2 × time 1-2 ] + [(MAP 2 +MAP 3 )/2 × time 2-3 ] + … + [(MAP 11 + MAP 12 )/2 × time 11-12 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, the cumulative BP determination was developed, which includes several BP measurements that take into consideration of both how high the BP levels have been and the duration of the high BP exposure before risk estimation. Several studies have simultaneously used the cumulative BP and baseline BP determinations to assess the effect of high BP on CVE occurrence, which showed that the association of the cumulative BP determination with CVE was stronger than the baseline BP determination (12)(13)(14)(15). Although cumulative BP seems to be superior than baseline BP in estimating CVE risk of high BP theoretically, no population studies have yet to verify this presumption.…”
Section: Introductionmentioning
confidence: 99%
“…HT on its own can also lead to endothelial dysfunction due to the increased shear force exerted on the vessel wall that the endothelium is exposed to. This can promote the formation of atheroma and indeed HT is a major risk factor for myocardial infarctions and cerebrovascular accidents [25]. Studies have shown that even modest increases in BP (stage 1 HT) are associated with an increased risk of cardiovascular events [26].…”
mentioning
confidence: 99%